1996
DOI: 10.3386/w5667
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants and Consequences of Financial Education in the Workplace: Evidence from a Survey of Households

Abstract: In recent years, the United States has witnessed significant growth in programs of financial and retirement education in the workplace. This phenomenon provides an opportunity to assess the effects of targeted education programs on financial choices. This paper uses a novel household survey to develop econometric evidence on the efficacy of employer-based financial education.While our primary focus concerns the effects of these programs on saving (both in general and for the purposes of retirement), we also ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 3 publications
1
45
0
1
Order By: Relevance
“…Lusardi (1999) further confirmed that households who spend time planning for retirement show a significant increase in their savings as compared to those who did not plan for retirement. Financial planning activities could include information seeking activities, for instance, meeting with a financial investment or retirement counsellor (Grable & Joo, 2001;Richardson, 1990), attending a financial seminar (Lusardi, 2003), or participating in a workplace retirement preparation program (Bernheim & Garrett, 1996;Madrian & Shea, 2001) which in turn stimulates saving practices (Gustman & Steinmeier, 2000).…”
Section: Retirement Planningmentioning
confidence: 99%
“…Lusardi (1999) further confirmed that households who spend time planning for retirement show a significant increase in their savings as compared to those who did not plan for retirement. Financial planning activities could include information seeking activities, for instance, meeting with a financial investment or retirement counsellor (Grable & Joo, 2001;Richardson, 1990), attending a financial seminar (Lusardi, 2003), or participating in a workplace retirement preparation program (Bernheim & Garrett, 1996;Madrian & Shea, 2001) which in turn stimulates saving practices (Gustman & Steinmeier, 2000).…”
Section: Retirement Planningmentioning
confidence: 99%
“…Bernheim and Garrett (1996) and Bayer, Bernheim, and Scholz (1998) find that financial education in the workplace increases participation in retirement plans.…”
mentioning
confidence: 99%
“…An alternative perspective with which to view the relationships between the variables of interest is that financial literacy and expectations for the future financial situation mediate the relationship between participation in the educational session and outcomes such as workplace satisfaction. To date, most of the research on workplace financial education has focused on its direct effects on financial behavior (Fletcher, Beebout, and Mendenhall 1997; Kim 2000), work outcomes (Joo 1998; Kim 2000), and personal saving (Bernheim and Garrett 2000, 2003). Little light has been shed on intermediate steps, such as the increase in financial literacy.…”
Section: Hypothesesmentioning
confidence: 99%